Evaluation of hot water and hot air heat shock treatments on South African avocados to minimise the occurrence of chilling injury - Kritzinger, Madeleine (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2002.